Multidimensional Validation of a HOTS-Based Negotiation Text Assessment for Senior High School Students - Subroto, Delya Cristiyani; Nuraeni, Ida (Jurnal Bahasa dan Sastra, 2026)
This study rigorously evaluates the content, construct, and criterion validity of an assessment instrument designed for negotiation text analysis. Employing a quantitative descriptive methodology, data were triangulated through classroom observations, pedagogical document analysis, and performance assessments involving 20 tenth-grade students. Findings demonstrate that the instrument exhibits robust content validity, aligning systematically with national curriculum standards. Regarding construct validity, expert panels yielded high ratings (scores 8–10), although items 2 and 5 required revisions due to identified explicit answer cues. Furthermore, criterion validity confirmed adherence to technical and ethical assessment standards, despite noted redundancies in the response options for items 8 and 9. All participants surpassed the minimum proficiency threshold of 70, with peak scores reaching 100. In conclusion, the instrument is categorized as valid and highly suitable for evaluating analytical competence, following minor refinements to specific items. This validation not only strengthens theoretical perspectives on multidimensional validity in language assessment but also offers practical guidelines for teachers in designing fair and curriculum-aligned negotiation text assessments in Indonesian senior high schools.